(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Over the past decade, Uzbekistan has undergone a fundamental transformation from a predominantly inward-oriented economic model to a more open, market-driven trajectory. Central to this shift has been the country’s strategic effort to deepen its engagement with international capital markets and strengthen its presence within the global emerging market (EM) fixed-income universe. As reforms accelerated particularly in foreign exchange liberalization, fiscal management, and state-owned enterprise restructuring Uzbekistan increasingly attracted the attention of global investors seeking new frontier-market opportunities. A defining feature of this integration has been the rapid expansion of Eurobond issuance across the sovereign and corporate sectors. The sovereign’s initial entry into global markets provided essential pricing benchmarks and signaled the government’s long-term commitment to transparency, market discipline, and global investor engagement. Building on this foundation, corporate issuers, first state-owned enterprises and subsequently private sector institutions began tapping international markets to diversify funding, strengthen balance sheets, and support investment programs.